Factors that positively influence adherence to antiretroviral therapy by HIV and/or AIDS patients and their caregivers - Andrew J. Ross; Myint Aung; Laura Campbell; Gboyega A. Ogunbanjo (AOSIS, 2011)
Background: The importance of dedicated adherence to antiretroviral treatment (ART) in the management of Human Immunodeficiency Virus (HIV) is well documented. Multiple factors may affect adherence and this study explores patients' and their caregivers' perceptions of factors which may positively influence adherence to ART. Method: This study was a descriptive, qualitative study that used both free attitude interviews and focus-group discussions. Nineteen patients attending a busy ART-clinic at a district hospital in KwaZulu-Natal and eight caregivers were purposefully selected. Selection criteria included good adherence to ARTs as evidenced by excellent clinic attendance for more than one year with evidence of clinical, immunological and viral improvement. Interviews were tape recorded, transcribed and thematically analysed. Results: Ten female participants, nine male participants and eight caregivers took part in the study. Participants highlighted three main categories that positively affect their adherence to ART namely: patient, disease and health care provider-related factors. Sub-themes included issues related to acceptance, disclosure to significant others, symptomatic improvement on ARTs and the importance of supportive relationships. Participants greatly valued the health care provider relationship and felt that the main role of the health care provider was to educate and support. Conclusion: This study has shown that the factors which most influenced adherence were patient-related (acceptance, disclosure, determination, and family support), disease-related and treatment-related (symptomatic illness and improvement on ARTs), and healthcare worker-related (relationships, and adherence classes).